Anesthetic management of a patient with Edwards syndrome. Issue 8 (23rd June 2016) - Mifsud, Stephanie; Bezzina, Maureen; Paris, Simon
Key Clinical Message: The use of suxamethonium in our case was uneventful and despite craniofacial anomalies, airway management was straightforward. This case illustrates that pediatric patients with trisomy 18, presenting with potentially acute life‐threatening conditions and requiring emergency major surgery can be managed successfully with a multidisciplinary approach. Abstract : The use of suxamethonium in our case was uneventful and despite craniofacial anomalies, airway management was straightforward. This case illustrates that pediatric patients with trisomy 18, presenting with potentially acute life‐threatening conditions and requiring emergency major surgery can be managed successfully with a multidisciplinary approach.